Utilizing Hospital Formulary System in Nepal - Khadka, Sitaram; Saeed, Hamid; Shahi, Janak; Bajgain, Yogesh; Yadav, Tank Prasad; Gupta, Ravi Prasad (Journal of Nepal Health Research Council, 2020)
Since the early 1950s, for medication management, the hospital formulary system subsisted as a list of drugs into the supply chain management process in hospitals. With the advent of pharmacy practice services, the system now is more oriented towards the rational use of drugs taking into account the safety of therapy, cost-effectiveness, and uninterrupted availability of drugs to improve and reflect upon the clinical judgment of healthcare professionals. Though very few hospitals in Nepal have adopted hospital formulary system, the perfect practice is still skimpy. The formation of drug and therapeutic committee along with the establishment of hospital pharmacy services is a growing trend with the arrival of hospital pharmacy guidelines 2072, thus, a positive spill-over of the hospital formulary system to each hospital in Nepal would be valuable in promoting rational drug therapy. Keywords: Cost-effectiveness; hospital formulary system, rational drug therapy.